1999
DOI: 10.1097/00000539-199901000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Capnography Monitoring During Neurosurgery

Abstract: This study, which aimed to reevaluate the ability of PETCO2 to estimate PaCO2 during neurosurgical procedures according to surgical position, indicates that PETCO2 cannot replace PaCO2 for the following reasons: scattering of individual values; occurrence of negative arterial to end-tidal CO2 gradient (P[a-ET]CO2; PaCO2 and PETCO2 variations in opposite directions; large changes in P(a-ET)CO2 between two samples; and instability of P(a-ET)CO2 over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…[13] Patient positioning has also been shown to have an impact on the accuracy of ET-CO 2 monitoring. [23] With patients undergoing renal or upper ureteral surgery in the supine position, Pansard et al reported that the ET-CO 2 to PaCO 2 difference was 4.8 ± 3.9 mmHg 10 min after induction and increased to 7.9 ± 3.5 mmHg ( P <0.01) 5 min after placement of the patients into the lateral decubitus ‘kidney rest’ position. Similar results were reported by Grenier et al in a cohort of patients undergoing neurosurgical procedures in the lateral decubitus position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13] Patient positioning has also been shown to have an impact on the accuracy of ET-CO 2 monitoring. [23] With patients undergoing renal or upper ureteral surgery in the supine position, Pansard et al reported that the ET-CO 2 to PaCO 2 difference was 4.8 ± 3.9 mmHg 10 min after induction and increased to 7.9 ± 3.5 mmHg ( P <0.01) 5 min after placement of the patients into the lateral decubitus ‘kidney rest’ position. Similar results were reported by Grenier et al in a cohort of patients undergoing neurosurgical procedures in the lateral decubitus position.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Grenier et al in a cohort of patients undergoing neurosurgical procedures in the lateral decubitus position. [3]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation of EtCO 2 and PaCO 2 has been reported to be unreliable in some clinical situations, and no correlation was found between EtCO 2 and PaCO 2 when the physiologic dead space was substantially elevated ( 13 - 19 ). Physiologic dead space ventilation is the sum of the anatomic dead space from the conducting airways and the alveolar dead space arising from a disease process and/or therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Both PEtCO 2 and PaCO 2 showed a significant rise from the supine position. Grenier et al [12] recorded a significantly higher P (a-Et) CO 2 gradient in neurosurgical patients operated in LDP in compared to those who were operated in the supine position (7 ± 3 mmHg vs. 6 ± 3 mmHg in lateral vs. supine position, P < 0.05). Similarly, Pansard et al [13] found a significant increase in P (a-Et) CO 2 gradient 5 min after LDP in comparison to the supine position (7.9 ± 3.5 mmHg vs. 4.8 ± 3.9 mmHg in lateral vs. supine position P < 0.05) in patients undergoing renal surgery in the LDP.…”
Section: Discussionmentioning
confidence: 99%